The Bulacan Hospital for tropical disease - Balanag, Andrei Florendo P.; Santos, John Ryan (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
Bulacan is being primed to be urbanized in the future and it is manifested through ongoing infrastructural work in many municipalities. However, due to the province's existing and unaddressed sanitation and public health issues such as flooding, weak waste management system and high infection rate, future dwellers are at risk of being susceptible to disease should more non-health inclined developments rise in the province. Unless there will be a change in perspective in urbanization, a health-crisis will ensue. The project acts as a first step solution to the province's dilemma. It envisions for a healthcare facility that responds, interacts, and protects existing and future dwellers of this province through the accessibility of specialized health service, and research. What is unique about this hospital is that public health education, through the facility's architectural setup and features, is a forefront service and opportunity for patients and visitors to learn more about practical sanitation, infection control, and public health in the simplest, easy-to-understand, and most engaging method. Through this kind of setup, a hospital can impact a person even beyond their stay in this facility and can act as a catalyst to the creation of more health-centered spaces.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Hospital facilities -- Bulacan; Healthcare facilities -- Bulacan